Biomechanical Quantification of Mendelsohn Maneuver and Effortful Swallowing on Pharyngoesophageal Function. (November 2017) - Doeltgen, Sebastian Heinrich; Ong, Ellisa; Scholten, Ingrid; Cock, Charles; Omari, Taher
Objective: To quantify the effects of 2 swallowing maneuvers used in dysphagia rehabilitation—the Mendelsohn maneuver and effortful swallowing—on pharyngoesophageal function with novel, objective pressure-flow analysis. Study Design: Evaluation of intervention effects in a healthy control cohort. Setting: A pharyngoesophageal motility research laboratory in a tertiary education facility. Subjects: Twelve young healthy subjects (9 women, 28.6 ± 7.9 years) from the general public, without swallowing impairment, volunteered to participate in this study. Methods: Surface electromyography from the floor-of-mouth musculature and high-resolution impedance manometry–based pressure flow analysis were used to assess floor-of-mouth activation and pharyngoesophageal motility, respectively. Subjects each performed 10 noneffortful control swallows, Mendelsohn maneuver swallows, and effortful swallows, with a 5-mL viscous bolus. Repeated measures analyses of variance was used to compare outcome measures across conditions. Results: Effortful and Mendelsohn swallows generated greater floor-of-mouth contraction ( P = .001) and pharyngeal pressure ( P < .0001) when compared with control swallows. There were no changes at the level of the upper esophageal sphincter, except for a faster opening to maximal diameter during maneuver swallows ( P = .01). The proximal esophageal contractile integral was reduced during Mendelsohn swallows ( P = .001). Conclusion: Effortful and Mendelsohn maneuver swallows significantly alter the pharyngoesophageal pressure profile. Faster opening of the upper esophageal sphincter may facilitate bolus transfer during maneuver swallows; however, reduced proximal esophageal contractility during Mendelsohn maneuver swallows may impair bolus flow and aggravate dysphagic symptoms.